2015
DOI: 10.1080/00087114.2015.1109933
|View full text |Cite
|
Sign up to set email alerts
|

Variations of morphology, ecology and chromosomes ofAconitum heterophyllumWall., an endangered Alpine medicinal plant in Himalayas

Abstract: Cytology, morphology and ecology were determined from 21 natural populations of Aconitum heterophyllum in Kashmir and Ladakh Himalayas. Data revealed a high body of variability among various morphological characters including plant height, foliage, floral and tuber attributes at intra-population levels. Plant height varied from 98 ± 4.6cm to 36.1 ± 4.5cm. The tuber crude drug production values ranged from 1.22 to 1.7 g/plant. It was generally lower at lower altitudes and higher at higher altitudes. The number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Such genetic differences have earlier been reported in different plant species by Baptista-Giacomelli et al (2000). According to Fadaei et al (2010), Saggoo and Farooq (2011), Kumar et al (2012) and Jeelani et al (2012Jeelani et al ( , 2014Jeelani et al ( , 2015, and cytomixis results in the production of unreduced gametes in several angiosperms or leads to the production of aneuploid plants. The formation of unreduced gametes is of evolutionary significance in a way that it can lead to the production of plants with higher ploidy level through polyploidization (Villeux 1985).…”
Section: Discussionmentioning
confidence: 64%
“…Such genetic differences have earlier been reported in different plant species by Baptista-Giacomelli et al (2000). According to Fadaei et al (2010), Saggoo and Farooq (2011), Kumar et al (2012) and Jeelani et al (2012Jeelani et al ( , 2014Jeelani et al ( , 2015, and cytomixis results in the production of unreduced gametes in several angiosperms or leads to the production of aneuploid plants. The formation of unreduced gametes is of evolutionary significance in a way that it can lead to the production of plants with higher ploidy level through polyploidization (Villeux 1985).…”
Section: Discussionmentioning
confidence: 64%
“…Baig et al [49] also recorded low density (0.56/m 2 ) of A. heterophyllum in Menwarsar, Kashmir. Further, Jeelani et al [50] revealed that populations of A. heterophyllum are not consistent as no subpopulations/pockets were expected to contain more than 250 mature individuals, and all the individuals of the species are in specific pockets in Kashmir Himalaya.…”
Section: Discussionmentioning
confidence: 99%
“…Conservation strategies for Aconitum should also involve a detailed study of its morphology, cytology, and ecology, as this information aids in designing a better conservation plan and increasing the understanding of the species. All morphological variability parameters, such as the plant structure, number of shoots and leaves, rhizome dimensions, plant height, leaf and flower dimensions, and number and size of seeds, should be considered altogether (Jeelani et al, 2015). The meiosis process in plants also requires cytological investigations since aberrant meiosis is a sign of ecological stress (Fuchs et al, 2018).…”
Section: Conservation Strategies Of Aconitum Sppmentioning
confidence: 99%
“…The meiosis process in plants also requires cytological investigations since aberrant meiosis is a sign of ecological stress (Fuchs et al, 2018). Abnormal meiosis includes cytomixis, chromosomal stickiness, chromatin fragmentation, unoriented bivalents, formation of chromosomal bridges, and chromosomal laggards (Jeelani et al, 2015). Such meiotic abnormalities give rise to nuclei of different sizes, rendering them sterile, which reduces the viability of the pollen, thereby creating morphological and genetic variations as observed in populations of A. heterophyllum (Jeelani et al, 2015).…”
Section: Conservation Strategies Of Aconitum Sppmentioning
confidence: 99%